Cathepsin-L influences the expression of extracellular matrix in lymphoid organs and plays a role in the regulation of thymic output and of peripheral T cell number - Lombardi, Gabriela (2005)
Nackt mice, which are deficient in cathepsin-L (CTSL), show an early impairment during positive selection in the context of class II MHC molecules and as a consequence, the percentage and absolute number of CD4(+) thymocytes are significantly decreased. In this study, we show that lymph nodes from nackt mice are hypertrophied, showing normal absolute numbers of CD4(+) T cells and marked increases in the number of CD8(+) T lymphocytes. Basal proliferative levels are increased in the CD4(+) but not in the CD8(+) population. Lymph node T cells show increases in the expression of alpha(5), alpha(6), and beta(1) integrin chains. These alterations correlate with increases in the expression of extracellular matrix (ECM) components in lymph nodes. Interestingly, laminin, fibronectin, and collagen I and IV are markedly decreased in nackt thymus which shows an augmented output of CD8(+) cells. These results demonstrate that a mutation in the Ctsl gene influences the levels of ECM components in lymphoid organs, the thymic output, and the number of T cells in the periphery. They further raise the possibility that, by regulating the level of expression of ECM components in lymphoid organs, CTSL is able to broadly affect the immune system.